Rhetorical Composition and Its Methodology in the Work of Ibn Rashiq al-Qayrawani al-Misili - Laouiji, Ahmed (El Omda in Linguistics and Discourse Analysis, 2021)
Abstract The book of “Al-omda” is considered as an encyclopaedia in poetry and its criticism and in rhetoric and its arts. It’s one of the most important literary,rhetorical, and critical sources.For the researchers and scholars, from various sectaries,it has an endless meaning, and they obtain from its literary prose, poetic, critical, or rhetorical contents. We’ve chosen from the predecessors’ opinions. In this book, the rhetorical lesson is mixed with the literary criticism so that they make a firmed relation,since rhetoric is important for the literary criticism, especially in the stage of emergence and development,and it’s one of its main basics. For the sake of revealing our literary, critical, and rhetorical heritage, we shall attempt inducing the book content through following the mechanisms used by Ibn Rashiq and his method in writing for refuting the accusation of collecting, and we shall effortfully bring together the different perspectives. Keywords: Al-omda, encyclopaedia, the rhetoric, the literary criticism, the research mechanisms, the method.